Iron–Titanium Oxide Nanocomposites Functionalized with Gold Particles: From Design to Solar Hydrogen Production. Issue 16 (20th July 2016) - Barreca, Davide; Carraro, Giorgio; Gasparotto, Alberto; Maccato, Chiara; Warwick, Michael E. A.; Toniato, Elisa; Gombac, Valentina; Sada, Cinzia; Turner, Stuart; Van Tendeloo, Gustaaf; Fornasiero, Paolo
Abstract : Hematite –titania nanocomposites, eventually functionalized with gold nanoparticles (NPs), are designed and developed by a plasma‐assisted strategy, consisting in: (i) the plasma enhanced‐chemical vapor deposition of α‐Fe2 O3 on fluorine‐doped tin oxide substrates; the radio frequency‐sputtering of (ii) TiO2, and (iii) Au in controlled amounts. A detailed chemicophysical characterization, carried out through a multitechnique approach, reveals that the target materials are composed by interwoven α‐Fe2 O3 dendritic structures, possessing a high porosity and active area. TiO2 introduction results in the formation of an ultrathin titania layer uniformly covering Fe2 O3, whereas Au sputtering yields a homogeneous dispersion of low‐sized gold NPs. Due to the intimate and tailored interaction between the single constituents and their optical properties, the resulting composite materials are successfully exploited for solar‐driven applications. In particular, promising photocatalytic performances in H2 production by reforming of water–ethanol solutions under simulated solar illumination are obtained. The related insights, presented and discussed in this work, can yield useful guidelines to boost the performances of nanostructured photocatalysts for energy‐related applications. Abstract : Fe2 O3 –TiO2 –Au nanocomposites with controlled spatial organization are fabricated by a three‐step plasma‐assisted synthetic strategy. Their high performances in solar‐driven H2 generation pave the way for energy generation from abundant and renewable natural sources.